Clinico-pathological changes in COVID-19 patients - Kumar, Shrawan; Pankaj, Pranjal; Singh, Narendra; Narang, Ajay; Anand, Pallavi; Singh, Desh Nidhi (International Journal of Advances in Medicine, 2021)
Background: Novel Corona virus is associated with the respiratory disorder. Corona virus cases disease ranging from a common cold like illness severe acute respiratory syndrome. Biochemical parameters become altered in the patients, and this has been correlated with the severity of the disease. The present study was undertaken to analyse the effect of novel corona virus infection in organs other than lungs. Methods: The study is a retrospective studycarried out in RMCH and RC, Kanpur from July 2020 to June 2021. Haematological, biochemical and inflammatory biomarker study was conducted in 336 COVID-19 patients. Results: Out of 336 COVID-19 patients the maximum number of patients belonged to the age group of 61-70 years. There were 75% symptomatic and 25% asymptomatic cases of confirmed COVID-19. Sore throat was the most common presentation followed by cough and dyspnoea. Other manifestations include fever, myalgia, loss of taste, loss of smell and running nose. Serum CRP and PCT concentration were observed in more severe cases 22.2% and 17% respectively. Haematological findings include decrease in total RBC count (58.33%). Symptomatic COVID-19 patients have thrombocytopenia (30.95%), lymphopenia (25%), leucocytosis (11.90%) and leucopenia 8.33%. Hepatic dysfunction and renal dysfunction was observed in 71.42% and 14.28% symptomatic cases respectively. Conclusions: We concluded that novel corona virus is not only affecting respiratory system but also other vital organs. On the basis of haematological and biochemical findings we can predict the severity of COVID-19 infection which could be helpful for management of the disease.